On Chinese learning strategies of learners from Central Asian countries: an analysis of gender, age, and learning duration effects - Chen, Ruiling; Zhang, Lirui (Frontiers in Psychology, 2024)
This research focuses on the Chinese learning strategies employed by learners from Central Asian countries, specifically examining the effects of gender, age, and learning duration. The study aims to identify and analyze the demographic factors that influence the learning approaches of these learners, providing insights for more effective teaching and learning of Chinese as a foreign language. Data are collected through questionnaires and interviews, and statistical analysis is conducted to explore the correlations between gender, age, learning duration, and learning strategies. The learning strategy model adopted in this study is based on Oxford's (1990) framework, which provides a comprehensive classification of language learning strategies. The results underscore the significance of incorporating these factors into language education programs, providing valuable insights into the unique needs and challenges encountered by learners from Central Asian countries. The findings indicate that students from Central Asian countries predominantly utilize social strategies, metacognitive strategies, and affective strategies in their Chinese language learning. These are followed by compensatory strategies, cognitive strategies, and memory strategies. While gender does not exert a significant impact on the utilization of Chinese learning strategies, there are discernible variations in memory and affective strategies between males and females. Age does not significantly affect overall learning strategies, but there are notable disparities in compensatory strategies among different age groups. Learning duration has a significant effect on compensation and metacognitive strategies. The correlation between learning duration and overall strategies is significant indicating that learners with different learning durations exhibit notable differences in compensation and metacognitive strategies.